On cross-sectional analysis in accounting research - Christie, Andrew A. (Journal of Accounting and Economics, 1987)
This paper examines cross-sectional analysis procedures common to many market-based accounting research papers. Both the economic and econometric properties of ‘levels’ and ‘returns’ studies are discussed. Topics covered include the relations between the accounting studies and cash flow valuation models, the role of expectations of accounting variables, deflators, spurious inference, risk adjustment and its relation to growth, size and leverage, residual dependence, dependence among explanatory variables, and the effect of scale differences across firms. Major conclusions are that market value is the correct deflator in returns studies, and that levels and returns studies are economically but not econometrically equivalent.